Representing reality; issues and concepts in documentary - Nichols, Bill (Bloomington : Indiana University Press, 1991)
The domain of documentary ## Documentary modes of representation ## Axiographics: ethical space in documentary film ## Telling stories with evidence and arguments ## Sticking to reality: rhetoric and what exceeds it ## The ract of realixm and the fiction of objectivity ## Pornography, ethnography, and the discourses of power ## Representing the body: questions of meaning and magnitude.
Onderzoek KASK (1KA-OFVR)
boek